Primary health care attributes and responses to intimate partner violence in Spain - Isabel Goicolea; Paola Mosquera; Erica Briones-Vozmediano; Laura Otero-García; Marta García-Quinto; Carmen Vives-Cases (Elsevier, 2017)
Objective: This study provides an overview of the perceptions of primary care professionals on how the current primary health care (PHC) attributes in Spain could influence health-related responses to intimate partner violence (IPV). Methods: A qualitative study was conducted using semi-structured interviews with 160 health professionals working in 16 PHC centres in Spain. Data were analysed using a qualitative content analysis. Results: Four categories emerged from the interview analysis: those committed to the PHC approach, but with difficulties implementing it; community work relying on voluntarism; multidisciplinary team work or professionals who work together?; and continuity of care hindered by heavy work load. Participants felt that person-centred care as well as other attributes of the PHC approach facilitated detecting IPV and a better response to the problem. However, they also pointed out that the current management of the health system (workload, weak supervision and little feedback, misdistribution of human and material resources, etc.) does not facilitate the sustainability of such an approach. Conclusion: There is a gap between the theoretical attributes of PHC and the "reality" of how these attributes are managed in everyday work, and how this influences IPV care. Resumen: Objetivo: Este estudio presenta las percepciones de profesionales de atención primaria sobre cómo los atributos de la atención primaria en España pueden influenciar las respuestas sanitarias a la violencia del compañero íntimo (VCI). Métodos: Estudio cualitativo con entrevistas semiestructuradas con 160 profesionales sanitarios de 16 centros de atención primaria en España. Los datos se analizaron con el enfoque de análisis de contenido. Resultados: Del análisis de las entrevistas emergieron cuatro categorías: Implicados/as con el enfoque de primaria, pero enfrentando dificultades para implementarlo; El trabajo comunitario depende del voluntarismo; ¿Trabajo multidisciplinario o profesionales que trabajan juntos?; y Continuidad amenazada por la sobrecarga de trabajo. Los participantes consideraron que la atención centrada en la persona y otros atributos del enfoque de atención primaria facilitaban la detección de VCI y una mejor respuesta a este problema. Sin embargo, también reconocieron que la forma en que se gestionan los servicios sanitarios (sobrecarga de trabajo, débil supervisión y escaso feed-back, distribución de los recursos humanos y materiales, etc.) no facilita la sostenibilidad de este enfoque. Conclusión: Existe una brecha entre los atributos teóricos de la atención primaria y la «realidad» de cómo estos atributos se gestionan en la actividad profesional del día a día y de qué manera esta influye en la atención a la VCI. Keywords: Primary health care, Intimate partner violence, Qualitative content analysis, Person-centred care, Palabras clave: Atención primaria de salud, Violencia de compañero íntimo, Análisis de contenido cualitativo, Atención centrada en la persona